2014
DOI: 10.1017/s0008423914000420
|View full text |Cite
|
Sign up to set email alerts
|

Balancing a House of Cards: Throughput legitimacy in Canadian Governance Networks

Abstract: This article examines the interaction of different modes and levels of legitimacy within network governance institutions over time. Drawing on new theoretical directions in European governance studies and empirical findings from Canada, we contend that whereas input legitimacy can be exchanged, or traded-off, with output legitimacy to reinforce the overall legitimacy of a network governance institution, “throughput legitimacy” functions as a necessary condition that sustains legitimacy over time. Through a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…This element of horizontal accountability is consistent with as the concept of “throughput legitimacy” (Schmidt ; Doberstein and Millar ), which shifts the analytical focus of social accountability from the static dimensions of input legitimacy (the representativeness of citizen influence on policy formulation) and output legitimacy (the effectiveness of the policy in achieving specified goals) to more dynamic dimensions of legitimacy that emphasize the quality of interactive and deliberative processes of policy design and implementation. This, along with Levesque's () four‐step method, provides a useful lens through which to view the critical elements in the design of networks for well‐functioning horizontal accountability.…”
Section: Five Lessons To Considermentioning
confidence: 76%
“…This element of horizontal accountability is consistent with as the concept of “throughput legitimacy” (Schmidt ; Doberstein and Millar ), which shifts the analytical focus of social accountability from the static dimensions of input legitimacy (the representativeness of citizen influence on policy formulation) and output legitimacy (the effectiveness of the policy in achieving specified goals) to more dynamic dimensions of legitimacy that emphasize the quality of interactive and deliberative processes of policy design and implementation. This, along with Levesque's () four‐step method, provides a useful lens through which to view the critical elements in the design of networks for well‐functioning horizontal accountability.…”
Section: Five Lessons To Considermentioning
confidence: 76%
“…This type of legitimacy signifies the quality of interactions between actors in the policy process (Schmidt, 2013: 6), and evaluating this type of legitimacy requires considering how governance arrangements work in practice (Schmidt and Wood, 2019: 728). The processes of decision making have thus become an emerging area of inquiry in Canadian and European governance contexts (for example, Doberstein and Millar, 2014; Howlett, 2000; Iusmen and Boswell, 2017; Levesque, 2012; van Meerkerk et al, 2015).…”
Section: Legitimacy In Decision Making and The Unique Status Of The Dmentioning
confidence: 99%
“…Apart from the structure of consultation, the potential for participatory instruments to produce legitimacy depends on the interaction dynamics between participants. For instance, it is suggested that principles of deliberation, such as communicative rationality, are ideal (Pratchett, 1999: 629; Ratner, 2008: 148), which are also identified as important qualities to produce throughput legitimacy (Doberstein and Millar, 2014: 266; Goodin and Dryzek, 2006). Nevertheless, it is acknowledged that consultation may also resemble utility maximizing bargaining or may be guided by organizational templates that are not amenable to learning or change (Montpetit, 2003: 98).…”
Section: Legitimacy In Decision Making and The Unique Status Of The Dmentioning
confidence: 99%
“…However, several studies have also recognised that merely focussing on input and output is insufficient if we are to fully understand the relation between legitimacy and public attitudes (Schmidt 2013;Doberstein and Millar 2015). To comprehensively explain why some systems perform better than others, scholars therefore propose also analysing throughput legitimacy, as distinct from traditional representation (input) or performance (output).…”
Section: Input Throughput and Output Legitimacymentioning
confidence: 99%